Influence of UV radiation and atmospheric factors on vapor permeability of thin-film modified polyethylene materials - Domantsevych, N.I.; Aksimentyeva, O.I.; Yatsyshyn, B.P. (Physics and Chemistry of Solid State, 2022)
The vapor permeability of modified polyethylene films after long-term exposure to UV radiation and atmospheric factors was studied. The dependences of changes in diffusion characteristics on the type of modifying additives and the time of action of external factors are established. It is shown, on the basis of polarographic studies, the reduction of the quantitative composition of volatile modifying components of the modified film under the action of UV radiation.